Assisted Natural Recovery: A Novel Approach to Enhance Diadema antillarum Recruitment - Hylkema, Alwin; Debrot, Adolphe O.; van de Pas, Esther E.; Osinga, Ronald; Murk, Albertinka J. (Frontiers in Marine Science, 2022)
The massive die-off of the sea urchin Diadema antillarum in 1983-1984 is one the main reasons for low coral recruitment and little coral recovery in the Caribbean. As natural recovery of D. antillarum is slow to non-existent, multiple restoration studies have been attempted. There are currently three different approaches to obtain individuals for restocking: translocation of wild-collected juveniles or adults, lab reared juveniles cultured from wild-collected settlers, or lab reared juveniles cultured from gametes. All three methods are costly and can only be applied on a relatively small scale. We here propose a fourth, new approach, which we term assisted natural recovery (ANR) of D. antillarum populations. ANR, a concept already applied in terrestrial restoration to restore forests and grasslands, can accelerate succession by removing barriers to natural recovery. In this study, performed on the Dutch Caribbean island of Saba, suitable settlement substrate was provided in the form of bio ball streamers that were attached to the reef shortly before the settlement season. At the end of the experiment, reefs with streamers had significantly higher D. antillarum recruit densities than control reefs without additional settlement substrate, indicating that the lack of settlement substrate is an important factor constraining natural recovery. However, the D. antillarum recruit abundance was low compared to measured settlement rates, possibly due to low post-settlement survival. The size distribution of recruits showed that recruits almost never became larger than 20 mm, which is likely due to predation. We conclude that, next to low settlement availability, also low post-settlement survival and high predation on recruits constrain natural recovery of D. antillarum populations on Saba. To improve survival of settlers till adults we propose to 1) reduce predation on settlers by using bio balls or other substrates that can provide shelter to larger individuals, 2) optimize the reef habitat by removing macroalgae, either manually or by facilitating other herbivores and 3) choose sites with a known lower predation density. The combination of these measures could improve prospects for ANR and we expect this new approach to contribute to recovery of D. antillarum populations in the future.